A rare presentation of superficial, inter-muscular, cystic, extra-spinal schwannoma over upper back - Srinjoy Saha (Neurologico Spinale Medico Chirurgico, 2020)
Schwannomas are rare tumours arising from peripheral nerve sheath and are usually related to the spinal cord and spinal nerves. Contrast magnetic resonance imaging (MRI) usually helps in establishing a pre-operative diagnosis. Rarely, their manifestation may be surprisingly new. Here, a 44-year-old lady came to our clinic with a painless asymptomatic progressively enlarging swelling over her upper back. It was fluctuant, with absent neural signs and symptoms. MRI showed a benign, purely-cystic, superficial-intermuscular, extra-spinal swelling near the upper thoracic vertebrae. However, classical diagnostic signs of schwannoma were absent. Complete surgical excision was performed with smooth dissection through a well-defined plane between the lesion and surrounding muscles. A 6.5x5.0x2.5 cm oval lesion with a glistening whitish-grey capsule was excised, and the deep wound was reconstructed in multiple layers. Interestingly, it was not attached to any identifiable nerves. Histopathology showed typical hallmarks like Antoni A regions and Verocay bodies. Positive S-100 staining during immunohistochemistry established its diagnosis as schwannoma. The postoperative one-and-half-year follow-up period was uneventful. Cystic schwannomas can surprise and confuse clinicians by arising anywhere in the body and with atypical manifestations. Surgeons need to consider it in the differential diagnoses of any undiagnosed slowly-growing swelling, including purely-cystic ones and perform careful surgical dissection to avoid any inadvertent nerve damage.